Determination of molecular types and genetic heterogeneity of Cryptococcus neoformans and C. gattii in Malaysia - Tay, S.T.; Lim, H.C.; Tajuddin, T.H.; Rohani, M.Y.; Hassan, Hamimah; Thong, Kwai Lin (Oxford University Press, 2006)
The molecular types and genetic heterogeneity of Cryptococcus neoformans and C. gattii clinical isolates in Malaysia were determined in this study. Of 44 C. neoformans collected between 1980 and 2003, 42 (95.5) were molecular type VNI, 2 (4.5) were molecular type VNII. Of 17 C.gattii isolates, 13 (76.5) were molecular type VGI, and 4 (23.5) were molecular type VGII. A difference was noted when comparing the molecular types of cryptococcal isolates in the earlier and recent cases of cryptococcosis. While both molecular types VNI and VGI were equally predominant in the earlier cases of cryptococcosis, VNI was the most predominant molecular type isolated from the recent cases. VNII was a new molecular type, isolated from 5.1 of the recent cases. All the bird dropping isolates were molecular type VNI. The genetic heterogeneity of the two predominant molecular types, i.e., VNI, VGI clinical isolates and bird dropping isolates of C. neoformans were further determined by polymerase chain reaction (PCR) fingerprinting method, using (GTG)5 as single primer. Two clusters of cryptococcal isolates were distinguished at 68.5 of similarity, with cluster I consisting of VNI isolates and cluster II consisting of VGI isolates. Each cluster was further subdivided into three subtypes at >/=80 of similarity. Fourteen bird dropping isolates were grouped into a subtype within VN1, sharing 82.7 of similarity with the clinical isolates. A higher degree of similarities, ranging from 93.4-97.6 was noted between 3 bird dropping isolates with the clinical isolates in another subtype. This study demonstrated the existence of various molecular types of C. neoformans isolates in Malaysia and the genetic heterogeneity within the predominant molecular types. The study also provides evidence for genetic relatedness of clinical isolates with bird dropping isolates in the environment.